A beautiful family : a novel [large type] - Trevelyan, Jennifer (Random House Large Print, 2025)
"Over the course of one sunbaked summer vacation, ten-year-old Alix is pulled into a web of mysteries she sets out to solve. A tense, page-turning debut of childhood, innocence, and evil. Alix is an observant kid. At ten, she catches more than her parents and older sister suspect. Over their summer break, Alix's mother plans to finish her novel, her father wants to grill and watch cricket, and her fifteen-year-old sister hopes to catch the eye of a local lifeguard. With everyone around her distracted, Alix and her new friend, Kahu, decide to solve a mystery that haunts this vacation community: they'll close the case of what happened to Charlotte, a child who was presumed drowned the year before. But things aren't quite as they seem, and as Alix and Kahu look for clues, they inadvertently dislodge information they wish they'd never uncovered. Are Alix's parents happy together? Is her sister putting her trust in the wrong people? Is their vacation rental as safe as it seems? And when someone else goes missing, Alix's family find themselves at the center of an urgent police investigation. Debut novelist Jennifer Trevelyan viscerally captures the special boredoms and frustrations of childhood, the fraught but unshakeable bond between sisters, and the dangers that lurk in the white lies we tell--especially about the people we love most"--